Research Capability and Professional Development Needs of Public School Teachers in Action Research: A Profile-Based Analysis - Jake M Laguador; John Rey SR Soverano (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aims to assess the professional development needs and research capability gaps of public elementary school teachers as a basis for developing targeted, evidence-informed interventions. Methodology: Quantitative research method was utilized in the study with 62 teacher-respondents using cross-sectional survey questionnaire to gather data in terms of profile and development needs in research within three weeks. Data were analyzed using descriptive and inferential statistics. Main Findings: The results revealed that teachers experience moderate to high research difficulty but are willing to engage in research capability training. They demonstrated a very high level of development needs in research across the six identified phases of the research program particularly the married teachers in conceptualization, production, and publication. Age, sex, and educational attainment do not significantly influence development needs, and research difficulty does not affect these needs, highlighting the necessity for targeted professional development. Novelty/Originality of this study: This study is novel in identifying elementary teachers’ specific research capability needs and using these insights to design a structured and contextualized training with mentoring support. By targeting skill gaps across all research phases, the program enhances teachers’ professional competence, contributes to human capital development, and strengthens a sustainable culture of research in the educational community.